2014
DOI: 10.1115/1.4026487
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Transient Hydrothermal Behavior of a Ferrofluid Flowing Through a Helical Duct in the Presence of Nonuniform Magnetic Field

Abstract: This paper investigates numerically the time dependent hydrothermal behavior of a ferrofluid (water and 4 vol. % Ee304) flowing in a helical channel, which is exposed to a nonuniform transverse magnetic field and its walls are subjected to uniform heat fiux. The PÄ'O phase mixture model and control volume technique have been used to study the flow. The results show that applying the nonuniform transverse magnetic field considerably increases the velocity and flow rate in the vicinity of the channel walls while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Aminfar et al [3] numerically examined the hydrothermal behaviour of water-based ferrofluid flowing through a helical channel using the CV technique. Transverse magnetic field was applied to the channel and increase in the flow rate and velocity gradient was observed with augmentation in heat transfer.…”
Section: Shakiba and Vahedimentioning
confidence: 99%
“…Aminfar et al [3] numerically examined the hydrothermal behaviour of water-based ferrofluid flowing through a helical channel using the CV technique. Transverse magnetic field was applied to the channel and increase in the flow rate and velocity gradient was observed with augmentation in heat transfer.…”
Section: Shakiba and Vahedimentioning
confidence: 99%
“…They found that applying a magnetic field leads to the formation of secondary flow and therefore increasing Nusselt number. The same group studied the influence of a transverse magnetic field on the ferrofluid mixed convection in a helical duct [20]. Their numerical results indicated that an applied transverse magnetic field increases the axial velocity of the ferrofluid near the walls, which leads to heat transfer enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Several numerical and experimental studies have been carried out, considering the ferrofluid's thermomagnetic convection in different geometries, by employing an external magnetic field . The flow and convection heat transfer of a ferrofluid, which was subjected to the magnetic dipole has been investigated by Strek and Jopek .…”
Section: Introductionmentioning
confidence: 99%